Answer:
= 1
Explanation:
The n th term of an arithmetic progression is
= a + (n - 1)d
where a is the first term and d the common difference
use the 9 th term and 7 th term to find a and d
= a + 8d =
→ (1)
= a + 6d =
→ (2)
Subtract (2) from (1) term by term
2d =
⇒ d =
![(1)/(63)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6j6k4nk2a7v554g9at33huegqdfh1x0poh.png)
Substitute this value into (2) and solve for a
a +
=
![(1)/(9)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bfzmi9kc8nsnnq4oe3fkodibqjfo3tui8b.png)
a =
-
=
![(1)/(63)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6j6k4nk2a7v554g9at33huegqdfh1x0poh.png)
Hence
=
+
= 1